Time for a Cyberweapons Treaty? - DUNCAN COLLUM, DANNY (Sojourners Magazine, 2015)
The author discusses Internet hacking and the concept of cyber warfare. Topics include a brief summary of the origin and evolution of the Internet, the incidences of hacking activities and cyber attacks among technologically developed nations, the aggressive policy adopted by U.S. President Barack Obama in preparation for future cyber warfare, and the author's recommendation for the creation of an international arms control policy for cyber weapons.